Case Report: Severe Immune-Related Cholestatic Hepatitis and Subsequent Pneumonia After Pembrolizumab Therapy in a Geriatic Patient With Metastic Gastric Cancer - Yang, Hui; Zhou, Chenfei; Yuan, Fei; Guo, Liting; Yang, Liu; Shi, Yan; Zhang, Jun (Frontiers in Medicine, 2021)
Background: Immune checkpoint inhibitors have provided significant clinical benefits to many patients with advanced cancer; however, severe immune-related adverse events (irAEs) have occurred. Detecting and treating irAEs early could improve patient prognoses. Therefore, clinicians and patients should understand that these irAEs exist, especially those that are rare and serious. Case Presentation: In this report, an 86-year-old male patient, diagnosed with metastatic gastric cancer involving the peritoneum and retroperitoneal lymph nodes was treated with 5-cycle pembrolizumab therapy (100 mg q 2 weeks), achieving a partial response. However, the patient developed Grade 3 cholestatic hepatitis and delayed pneumonia 10 days and 2 months after the final pembrolizumab dose, respectively. After discontinuing the pembrolizumab therapy and excluding obstructive jaundice with imaging studies, the patient received steroid therapy, with a gradual symptom improvement. However, the patient developed delayed pneumonia with type 1 respiratory failure one-month post-discharge. Several microbiologic tests were negative, and immune-associated pneumonia was suspected, but we could not exclude an opportunistic infection. The patient recovered with steroids and antibiotics and remained in partial remission 5 months after pembrolizumab withdrawal. Conclusions: Cholestatic hepatitis is a rarely reported toxicity of immune checkpoint inhibitors, which should be suspected and addressed once obstructive jaundice is ruled out. In addition, clinicians should be aware that irAEs can occur at any time in patients treated with immune checkpoint inhibitors and that a timely diagnosis should be made.